RETROSPEKSI MAKNA SISTEM PRESIDENSIL DI INDONESIA TERHADAP PRO DAN KONTRA PEMILU SERENTAK DALAM RANGKA MENUJU KONSOLIDASI SISTEM DEMOKRASI MELALUI REFORMASI PEMILU - Malik Ibrahim (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
Amandement of Constitution Republik Of Indonesia 1945 resulting the happening of change in system arrange state among others referring to admission filling of certain political position through direct general election. Code arranging to regarding General election of President and Vice President meant to affirm system of presidential which effective and strong. Procedures and mechanism of Legislative and President General election which have been arranged to invite a number of pros and contra by citizen. there wishing execution of done Legislative General election at a time with General election of President according to rule of Section 22E sentence (1) and sentence (2) Constitution Republik of Indonesia 1945. Opinion which pros and contra, it true can be accepted, because in a election system of course will there are weakness and kindliness it.